Treatment of mucosa associated lymphoid tissue lymphoma with a long‐term once‐weekly regimen of oral azithromycin: Results from the phase II MALT—A trial. Issue 1 (19th September 2018) - Lagler, Heimo; Kiesewetter, Barbara; Dolak, Werner; Obermueller, Markus; Simonitsch‐Klupp, Ingrid; Lukas, Julius; Neuper, Ortrun; Lamm, Wolfgang W.; Mayerhoefer, Marius E.; Raderer, Markus
Abstract: The macrolide clarithromycin has been reported as active for therapy of mucosa associated lymphoid tissue (MALT) lymphoma. Pharmacokinetic properties, however, require continuous daily intake over a prolonged period of time. As the macrolide azithromycin is characterized by a long half‐life as well as potential antineoplastic activity in vitro, we have performed a phase II trial of long‐term once‐weekly oral azithromycin for treatment of MALT lymphoma. In a 2‐stage‐design, 16 patients (10 f/6 m) with histologically verified and measurable MALT lymphoma were included in the first phase of the trial, which could be expanded to a maximum of 46 patients depending on remissions in the first phase. Patients were given oral azithromycin 1500 mg once‐weekly 4 times a month, and restaging was performed after 3 and 6 months. Two patients had gastric and 14 extragastric MALT lymphoma; 12/16 patients were treatment‐naive and received azithromycin as first line treatment. Tolerance of this regimen was excellent, and 14/16 patients received 6 months of treatment as scheduled, while 1 patient each discontinued after 4 (progressive disease) and 1 cycle (personal reasons), respectively. The most commonly observed side effects were mild nausea (n = 8) and diarrhea (n = 4). Efficacy, however, was low as only 4/16 patients (25%) responded, with 2 complete and 2 partial remissions, 9 patients (56%) had stable disease, and 3 patients 19%) were rated as progressive disease. As the predefined activity of more than 7/16 patients responding was not reached, the study was stopped after 16 patients. Although long‐term once‐weekly oral azithromycin showed some antilymphoma activity, the response rate was below the predefined threshold of interest. However, based on our data, one cannot rule out suboptimal dosing in our study; attempts to study azithromycin at a different mode of application might be warranted in the future.